Burnout, empatia e autoeficácia em estudantes de enfermagem em universidades estaduais do Paraná - Lopes, Adriana Rezende (2018)
Work activities in the health area have been related to greater vulnerability to burnout, including students, when they begin to experience the profession in the supervised stages. Studies have sought to understand the influence of empathy or self-efficacy in the development of burnout. This study aimed to analyze burnout, empathy and self-efficacy in the context of nursing students from State Universities of Paraná, starting from the third year of graduation. For this study, the validated versions for use in Brazil of the Maslach Burnout Inventory (MBI), Interpersonal Reactivity Index (IRI), Occupational Self-Efficacy Scale - Short Form (OSS-SF) were used, as well as a questionnaire with sociodemographic, academic, work and health variables. Descriptive and analytical statistics were performed, with a significance level of α<0.05. Cronbach's alpha coefficient was used to evaluate the reliability of the scales, and the Kolmogorov-Smirnov test was used to test the normality of the data. Pearson Chi-Square, Fisher's exact test, Student's T test, Mann-Whitney, Anova, Kruskal-Wallis, Dunn's Post-test, Spearman's Correlation and Multivariate Logistic Regression were used in this study. After the approval by the Ethics Committee in Research with Human Beings of Unioeste, the data collection was performed from June to September 2017. Participants of the study were 323 students from six nursing courses from five State Universities, with 12.2% of data loss. The convenience sample consisted of 284 participants, mostly: women (90.1%), between 18 and 24 years old (77.5%), unmarried (83.8%), without children (88.7%), living with relatives (68.6%) and family income up to three minimum wages (56.0%), non-smokers (93.7%), non-regular physical activity (66.2%), doing one period of internship (71.5%), with a weekly workload of up to 24 hours (58.1%) and on-site training less than three months (84.5%). The prevalence of high burnout was 6.0%, with 36.3% of high Emotional Exhaustion, 37.7% of high Depersonalization and 28.2% of Low Personal Realization. The absence of regular physical activity and weekly workload of more than 24 to 40 hours per week were predictive of burnout and emotional exhaustion. The affective and cognitive dimensions of empathy (Empathic Consideration and Perspective Consideration) correlated positively with each other and tended to grow or decrease in the same direction. Self-efficacy and Empathy seemed to contribute to the prevention of burnout, insofar as greater self-efficacy was associated with lower Emotional Exhaustion, greater Empathy (cognitive and affective dimensions) were associated with less Depersonalization, and both, greater Empathy and greater Self-efficacy, were significantly associated with greater Personal Realization. The results of the study pointed out the worrying risk of developing burnout among students, due to the high rates of Emotional Exhaustion and, especially, in the case of nursing students, of Depersonalization, which directly affects the essence of care and the humanist profile aimed at the profession.